PERILAKU MAKAN DAN AKTIVITAS FISIK IBU RUMAH TANGGAYANGKEGEMUKAN DAN OBESITAS DI KELURAHAN BUNGA TANJUNG KECAMATAN DATUK BANDAR TIMURKOTA TANJUNGBALAI - Nur Arsi; Fitri Ardiani; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Obesity ranks the fourth leading cause of death in the world. In Indonesia the prevalence of overweight people is 13.5% and the prevalence of obese people is 15,4%. North Sumatra is ranked eighth in obesity and low physical activity from 2007 to 2013. Tanjungbalai is ranked seventh in obesity and ranked fifth in terms of low physical activity. The purpose of this research is to know the description of eating behavior and physical activity of overweight and obese housewife in Kelurahan Bunga Tanjung Datuk Bandar Timur Tanjungbalai City. This research method is descriptive with cross sectional research design and sampling technique is done in total sampling that is counted 94 people,which is 56 people get overweight and 38 people get obesity, with the research population counted 1,510 people. The results showed that the level of knowledge of housewife about overweight and obesity in good category for 80 people (85,1%), attitudes of respondents also are in enough good for 94 people (100%), respondent action is in category Less for 90 people (95,7%), and physical activity of respondent is in light category for 81 person (86,2%), and no one context about behavior and physical activity of housewife about the overweight and obesity occured. From the results of research suggested to the relevant institutions for the prevention of overweight and obesity in housewives are more increased by doing counseling and counseling to housewives, then to housewives to be more active to find out information about balanced nutritious food and the need to perform physical ctivity such as on foot more than by transportation. Keywords : Eating Behavior, Housewife, Physical Activity, Overweight, Obesity